Influence of the Milking Units on the Pulsation Curve in Dairy Sheep Milking - Caria, Maria (Animals (Basel), 2020)
SIMPLE SUMMARY: In dairy farms, the mechanical milking process represents one of the most delicate activities as it may affect the quantity and quality of the milk produced and the animals’ welfare. Mechanical milking systems can be designed with different components (milking units, liners, etc.) and configured with different operative parameters (vacuum level, pulsator rate, etc.) that may significantly influence the milking performances. Thus, the aim of this study was to analyze nine milking units to evaluate the effects of the volume of the pulsation chamber, the touch point pressure of the liners and the operative parameters of the milking system, on the duration of the increasing and decreasing vacuum phases of the pulsation curve. The results obtained underlined that the characteristics of the milking units affected the pulsation curve. Specifically, the pulsation chamber volume and the pulsator rate were strictly related to the duration of the phase of milking and massage. Contrary to expectations, the touch point pressure of the milking liners was not related to the length of the increasing vacuum phase and the decreasing vacuum phase (phase “a” and “c”). This study underlined how the configuration of the mechanical milking system and the characteristics of the components installed may influence the proper length of each phase of the pulsation curve. ABSTRACT: Mechanical milking is a critical operation in ewe dairy farming where the operative parameters and the milking routine strongly influence milk production and animal welfare. The challenge in adapting dairy animals to the farm environmental conditions may cause illness and compromise the quality of the products. From this perspective, it is important to evaluate the technological and operational aspects that can influence milk quality and animal welfare. Thus, the aim of this work was to investigate the effects on the pulsation curve of several teat cup characteristics (volume of the pulsation chamber) at determined operating parameters (vacuum level and pulsator rate) recorded from nine different milking units. Moreover, the touch point pressure of different liners was measured. Data analysis showed that the sheep milking unit characteristics affected the pulsation curve significantly. The length of both the increasing vacuum phase and the decreasing vacuum phase (phase “a” and “c”, respectively), which affect the milking and massage phases, was directly related to the pulsation chamber volume (R(2) = 0.86) and the pulsator rate. No relationship emerged between the touch point pressure and specific characteristics of the liners such as the material, the shape, the diameter, the length, or the extension of the body. Considering the delicate role that the pulsation plays in ensuring animal welfare during milking, it is important to take into account the complete configuration and operative characteristics of the milking units. This will ensure that the complex interaction between the pulsation system and the milking units is considered when planning and assembling milking systems.